Formulation and evaluation of an automatic dishwashing detergent containing T1 lipase - Abdul Rahman, Izuddin (2013)
Due to the concerns on the environment, the detergent industry is required to take more environmentally friendly approaches in formulating detergents, which include using biodegradable chemicals and enzymes. As a result, the use of enzymes in detergent formulation has become a must, and enzymes of many types and functions are being developed. Consequently, a recombinant enzyme called T1 lipase (E.C.3.1.1.3), which has been well-studied and successfully produced, was evaluated as a detergent enzyme for automatic dishwashing detergent (ADD) formulation. T1 lipase was mass produced at shake flask scale by growing the Escherichia coli BL21 expression host, which carried the T1 gene and harvesting the crude T1 lipase from the bacterial cells through sonication. The enzymatic activity was assayed, and the presence of the enzyme was confirmed using sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE). The crude enzyme was not purified to its homogeneity, but the presence of the host proteins was assumed not to give any significant effect to the subsequent results of this study, which was proven by the absence of the lipases, amylases, and proteases from the host organism. The crude T1 lipase in its free form was then checked for compatibility with the detergent components by conducting stability tests and checking its residual enzymatic activity. T1 lipase was mostly stable in nonionic surfactants, especially those that are made of polyhydric alcohols. T1 lipase was also stable in a mixture of sodium carbonate and glycine, which yielded pH 9.25 close to T1 lipase optimum pH of 9.0. However, sodium carbonate alone destabilized T1 lipase possibly due to the interaction between carbonates and Ca2+. These results indicated that polyhydric alcohols and glycine had stabilizing effects on T1 lipase. Next, the crude T1 lipase was spray-dried with the addition of wall materials, such as gum arabic and maltodextrin. A blend consisting of gum arabic/maltodextrin/T1 lipase supernatant with a ratio of 6:12:3 produced products that were mostly spherical when viewed under an electron microscope, and the encapsulated T1 lipase yielded a three-fold increase in enzymatic activity compared to the free T1 lipase. The spraydried product was also more soluble due to the hydrophilic nature of the wall materials Subsequently, the crude T1 lipase was evaluated as an auxiliary component for ADD formulations. The dishwashing performance of the formulated ADDs was evaluated in term of percent soil removed using the Leenert‘s Improved Detergency Tester. The dishwashing performance of the formulated detergent was positively affected by the increase in temperature but negatively affected by the presence of hard water, specifically Ca2+ and Mg2+. The presence of hard water reduced the efficiency of the formulated ADDs in removing soil by an average of 68%. However, T1 lipase was not negatively affected by the presence of hard water, and this enzyme was enhanced by the presence of polyacrylates. Moreover, the presence of Ca2+ improved the structural integrity of T1 lipase, especially at elevated temperature. Ultimately, an ADD formulation dubbed as ―U1‖ was produced based on the results of this study. Overall, the addition of T1 lipase to the ADD formulations indicated an improved dishwashing performance of up to 17% compared with the absence of T1 lipase, especially in the presence of hard water. Furthermore, this study will give more insight on lipase as detergent enzyme, specifically in automatic dishwashing.